Spatial ecology of non-breeding Eurasian Griffon Vultures Gyps fulvus in relation to natural and artificial food availability. Issue 1 (2nd January 2020) - Genero, Fulvio; Franchini, Marcello; Fanin, Yannick; Filacorda, Stefano
ABSTRACT: Capsule: The movements and spatial ecology of non-breeding Eurasian Griffon Vultures Gyps fulvus in northern Italy, Croatia and Austria do not seem to be affected by feeding station use. Aims: The purpose of this study was to assess how the creation of a feeding station at the Riserva Naturale Regionale del Lago di Cornino (Forgaria nel Friuli, northeast Italy) during the 1980s might have affected the spatial and behavioural ecology of the Eurasian Griffon Vulture. Methods: Using global positioning system (GPS) satellite tracking, we studied movements of nine non-breeding Eurasian Griffon Vultures within the Riserva Naturale Regionale del Lago di Cornino in Italy, the Hohe Tauern in Austria and the Kvarner Gulf in Croatia. Results: Both the average foraging range size and the time spent by the birds in Italy were comparable to those recorded in Croatia and Austria, where the vultures depend on unpredictable food resources. A significant difference in terms of foraging range size was recorded among seasons. In winter it seems to be smaller as a consequence of reduced movements performed by the individuals due to harsh climate conditions. Conclusions: Our results suggest that the creation of a feeding station in Forgaria does not seem to have affected the spatial ecology of the Eurasian Griffon Vulture. However, due to the limited sample size and the young age of the individuals monitored, which have a long dispersal period, the findings presented should be considered as preliminary. Further research needs to be implemented to inform decisions regarding the management of supplementary feeding stations to promote the recovery and conservation of scavenger species, particularly in areas in which they have declined massively.